Design and performance test of a water hyacinth (Eichhornia crassipes) and coconut shell charcoal briquette mixing machine - Rohmat, Yusup Nur; Kusmayadi, Adi; Sugara, Ferry; Apriansyah, Riza; Agustin, Neli (Politeknik Negeri Lhokseumawe, 2026)
Dependence on fossil fuels such as oil and natural gas gives rise to various problems, including rising energy prices, limited supply, and environmental impacts in the form of high carbon emissions. Therefore, efforts are needed to develop alternative energy sources based on local raw materials such as biomass briquettes which can be made from various organic waste, such as water hyacinth and coconut shells. The objectives of this research focus on the design, manufacture, and performance testing of briquette mixing and molding machines, as well as analysis of the quality of briquettes produced from a mixture of coconut shell charcoal and water hyacinth with the addition of paraffin wax as an adhesive. The machine was designed using dimensions of 1000×500×500 mm, equipped with a spiral mixer supported by an S45C steel shaft. This research presented a method of making briquettes with various compositions of water hyacinth and a mixture of coconut shell charcoal and paraffin wax as adhesives, and tested for calorific value, ash content, and combustion rate. The best results were obtained from a mixture of 70% coconut shell charcoal, 30% water hyacinth, and 5% paraffin wax, with a calorific value of 6.285 cal/g, an ash content of 2%, and a stable combustion rate of 0.12–0.16 g/min. The addition of paraffin wax has been shown to improve combustion stability and energy efficiency. The research results show that the designed mixer and briquette press machine function effectively, and briquettes made from biomass waste with natural adhesives have great potential as an environmentally friendly and economical alternative fuel.